Chinese Journal of Applied Linguistics (De Gruyter Mouton, 2011)
The Chinese Journal of Applied Linguistics is the only English language teaching (ELT) journal in China that is published in English, serving as a window to Chinese reform on ELT for professionals in China and around the world. The journal is internationally focused, fully refereed, and its articles address a wide variety of topics in Chinese applied linguistics, including the topics of language education and second language acquisition.